Peran Jamaah Yasinan Sebagai Pusat Pemberdayaan Masyarakat Dusun Krajan Desa Karangpatihan Kecamatan Pulung Ponorogo - Yusuf Maulana; Ibnu Muchlis (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Building strength through the yasinan tradition, in general, yasinan is only an association and limited to ordinary religious rituals, even though that is where there is potential in gathering village communities, especially Yasinan in Krajan Hamlet, Karangpatihan Village, Pulung Ponorogo District, East Java. Since the beginning, the Jamaah management realized that from a number of media and da'wah methods carried out in a period of 33 years (1990-2023), Yasinan's activities were considered the most successful in bringing about the transformation of the ummah. abangan society became a religious society. Members want to develop the role of Jamaah Yasinan to become a religious ritual activity, social religion and at the same time a center for community empowerment in the global era. Efforts to develop members in empowering and enhancing the role of Jamaah Yasinan as a Center for Community Empowerment.